Can crosslinking improve both CO2 permeability and plasticization resistance in 6FDA-pBAPS/DABA copolyimides? - Balcik, Marcel; Velioglu, Sadiye; Tantekin-Ersolmaz, S. Birgul; Ahunbay, M. Goktug (Elsevier Sci Ltd, 2020)
In membrane-based CO2 separation, glassy polymeric materials suffer from plasticization phenomenon. To suppress plasticization, cross-linking is a possible remedy, which however alters the separation performance significantly. This study investigates the effect of crosslinking on the CO2 transport properties and plasticization resistance of 2,2'-bis-(3,4-dicarboxyphenyl) hexafuoropropane dianhydride - bis [4-(4-aminophenoxy) phenyl] sulfone/3,5-diaminobenzoic acid (6FDA-pBAPS/DABA) copolyimide using molecular modeling and simulation tools that integrate quantum level calculations with Molecular Dynamics (MD) and Monte Carlo (MC) simulations. Mimicking the thermal crosslinking procedure, 25, 50, 75, and 100% crosslinked copolyimide structures are constructed for sorption and diffusion simulations and compared with the uncrosslinked polymer. The increased glass transition temperature of the polymers with crosslinking density confirms enhanced rigidity due to crosslinking, which reduces the packing efficiency of polymer chains and leads to higher fractional free volume, hence increasing the CO2 diffusivity. Analyses of CO2-accessible free volume evolution as a function of pressure show increased plasticization resistance with crosslinking. However, radial distribution function analyses indicate that crosslinking reduces the number of preferential sorption sites for CO2 molecules and prevents also the expansion of free volume elements around these sites. Consequently, CO2 solubility of the polymers decreases while diffusivity increases with increasing crosslinking density. This study reveals that the resultant effect of thermal crosslinking on 6FDA-pBAPS/DABA copolyimide is an increase in both CO2 permeability and plasticization resistance, which are the most desirable properties in CO2 separation applications.
Keywords: Molecular simulation; Copolyimide; Membrane-based gas separation